Money in Islamic Legal Discourse: Concepts and Practices - Oberauer, Norbert (La moneta di Dio, 2022)
The present article is an introduction to the Islamic legal discourse on money. It focusses primarily on the doctrinal conceptualization of money, but also on legal and commercial practice. I argue that the Islamic discourse on money is characterized by a tension between doctrinal tenets and practical requirements, which often forced jurists to compromise. The article adresses both the traditional legal doctrine as well as discussions on modern phenomena such as paper money and cryptocurrencies.